Early genetic diagnosis of thymidine kinase 2-related mitochondrial DNA depletion syndrome in a neonate with respiratory failure: A rare case highlighting the role of early genetic diagnosis and ethical decision-making - kumar, mukesh; Iqbali, Tauhid; Singh, Harpreet; Shah, Ravi (Indian Journal of Case Reports, 2026)
Mitochondrial DNA (mtDNA) depletion syndromes represent a heterogeneous group of autosomal recessive disorders characterized by a significant reduction in mtDNA copy number, leading to impaired oxidative phosphorylation and severe multisystem disease. The myopathic form caused by mutations in the thymidine kinase 2 (TK2) gene is particularly rare and often presents in infancy with profound muscle weakness and respiratory failure. We report a rare case of infantile-onset TK2-related mtDNA depletion syndrome presenting in the immediate neonatal period with severe hypotonia and respiratory failure. Early genetic diagnosis enabled appropriate counseling and facilitated informed decision-making by the family. This case underscores the importance of considering mitochondrial disorders in neonates with unexplained hypotonia and respiratory insufficiency.